Analysis of the Assimilation Process of Banking and Financial Terminology from Russian to Uzbek - Qutliyeva , Muhayyo (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article investigates relationships among terms, identifying synonymous, antonymous, homonymous, and polysemantic terms. Such relationships not only illustrate the complexity of the banking and financial terminology system but also reflect broader linguistic trends across various subsystems. Through this analysis, we aim to contribute to a deeper understanding of how economic language evolves through cultural and linguistic exchanges, ultimately enriching both the Uzbek language and its financial discourse.